Pioneering women archivists in early 20th century England - Shepherd, Elizabeth J., 1960- author. Link Link
1 online resource (240 pages)
Keywords: This book tells the story of four remarkable women who laid the foundations of English local archives in the early 20th century: Ethel Stokes, Lilian Redstone, Catherine Jamison and Joan Wake. The book analyses their professional historical work, alongside their educational, social and family contexts, to reveal their place in the history of the archival profession.Although this book focuses on the history of archives in early 20th century England and on the contribution of women, it will also be of interest to anyone interested in the history of archives internationally. The book makes a new contribution to the growing literature about the role of women in the development of modern professions, such as medicine, nursing and psychoanalysis, and of disciplines including history, philosophy, literary and musical composition. It brings out the hidden voices of women in archival history which has previously been the history of great men, institutional archives, government commissions and reports and professional infrastructure. It also tells the story of women's struggle for independence and education, of the ways in which women established independent cultural, social and family networks and shows how these women used their scholarly skills to earn a living.The book will be of interest to archivists and records professionals in England and internationally; to students who are studying archives, records management, library science, cultural studies and related disciplines; and to historians in cognate fields such as feminist history, cultural studies, literary studies and biography.